On Restricted Detour Median of Special Graphs - Rasha S. Hasan; Haitham N. Mohammed; Ahmed M. Ali (International Journal of Mathematics and Mathematical Sciences, 2025)
The restricted detour distance between two vertices is the length of longest path P such that the induced subgraph for a vertex set of P is identical P. The number of restricted detour distance of a vertex v of a connected graph Ǥ is a summation of restricted detour distances from v to all vertices of Ǥ. In this paper, we give a new definitions called restricted detour median graph (RDM-graph) and restricted detour self-median graph (RDSM-graph) and then we find many results related with them.